Musculoskeletal Disorders Among Greek Physiotherapists: Traditional and Emerging Risk Factors - I.D. Anyfantis; A. Biska (Elsevier, 2018)
Background: Musculoskeletal disorders (MSDs) in the health industry are quite common, however, there have only been a few studies regarding physiotherapists, while in Greece, there is an apparent lack of research and data. The aim of this study is to investigate MSDs experienced by physiotherapists in Greece, their causes and specific measures, and good practices followed. Additional emerging risk factors will be examined. Methods: A questionnaire of MSDs followed by individual and workplace characteristics was completed by 252 physiotherapists. It covered the major workplace categories such as public hospitals, private rehabilitation centers, and private practices. Results: Analysis indicated that 89% of the respondents had experienced a work-related MSD; 32.2% of those injuries occurred within the first 5 years of working. The most lumbered physiotherapists were those working as private practitioners and almost half of the injured respondents chose to work while injured. The most common measure taken to tackle work related MSDs was found to be physical therapy sessions. Job satisfaction and psychosocial issues were also identified as side-effects of the economic slowdown. Conclusion: Physiotherapists in Greece were found to suffer from MSDs; workplace musculoskeletal injuries were quite common but under-reported. The body parts most affected were the lower back, the upper back, the shoulders, and the neck. There was a strong correlation between the workplace setting and the number of MSDs. A well-defined occupational safety and health management system and strict administration steering were found to reduce MSDs. The economic slowdown experienced in Greece during the execution of this study placed additional pressure on physiotherapists. Keywords: Musculoskeletal disorders, Occupational health, Physiotherapists, Risk factors